Factors Influencing Dental and Oral Health and Access to Dental Care in Indonesian Coastal Communities: A Literature Review - Muh Fajrinshadiq Rusli Fajrin; Harniati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Oral and dental health remains a significant public health concern in developing countries, including Indonesia. One of the most prevalent issues is the high incidence of dental caries, particularly in coastal communities. Various factors contribute to this condition, such as educational level, health knowledge, lifestyle, dietary patterns, cultural practices, and geographical conditions. Coastal communities are often highlighted in health studies due to their role as primary contributors to national protein intake through fishing activities. However, their oral health status is frequently neglected, despite their unique environmental and social characteristics that may increase health risks. Objective: This study aims to identify the factors influencing oral health and the prevalence of dental caries in Indonesian coastal communities. Methods: A Systematic Literature Review (SLR) was conducted by collecting and analyzing relevant articles from databases such as Google Scholar and ResearchGate. The journal selection process followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, focusing on studies related to oral health and dental caries in coastal populations. Results: The review identified several contributing factors to poor oral health and high caries incidence, including age, fish protein consumption, access to healthcare services, poor clean water quality (habitual use of rainwater and well water), exposure to fish smoking fumes, smoking, alcohol consumption, parental education level, and infrequent tooth brushing. The most dominant factor was poor water quality. Conclusion: Comprehensive strategies are needed to address these multifactorial risks and improve oral health in coastal communities. Keywords: Indonesia, Oral Health, Dental Caries, Coastal Communities